Queer Girls, Temporality and Screen Media Not 'Just a Phase' - Monaghan, Whitney; SpringerLink (Online service) (London : Palgrave Macmillan UK(Imprint), 2016)
This book takes up the queer girl as a represented and rhetorical figure within film, television and video. In 1987, Canada's Degrassi Junior High featured one of TV's first queer teen storylines. Contained to a single episode, it was promptly forgotten within both the series and popular culture more generally. Cut to 2016 - queer girls are now major characters in films and television series around the globe. No longer represented as subsidiary characters within forgettable storylines, queer girls are a regular feature of contemporary screen media. Analysing the terms of this newfound visibility, Whitney Monaghan provides a critical perspective on this, arguing that a temporal logic underpins many representations of queer girlhood. Examining an archive of screen texts that includes teen television series and teenpics, art-house, queer and independent cinemas as well as new forms of digital video, she expands current discourse on both queer representation and girls' studies by looking at sexuality through themes of temporality. This book, the first full-length study of its kind, draws on concepts of boredom, nostalgia and transience to offer a new perspective on queer representation in contemporary screen media.
Acknowledgements -- List of Illustrations -- Just a phase -- 1: "Are Queer girls, girls?" -- 2: Serialising the queer girl in Sugar Rush and Skins 3: Retrospective narratives, nostalgia and the queer girl: For 80 Days and Butterfly -- 4: On boredom, love and the queer girl: My Summer of Love, Show Me Love -- 5: Time imagined queerly in mashup videos -- Beyond Girlhood -- Appendix - 15 years of Queer Girls, 1998-2013 -- Works cited -- Select Filmography .
Keywords: Motion pictures; Motion picture acting; Film Theory; Media Studies; Gender Studies; Screen Performance